Barriers and facilitators in continuous medical education related to allogeneic stem cell transplantation: a qualitative study of physicians - Eickmann, Sascha; Wolff, Daniel; Kobbe, Guido; Dreger, Peter; Kröger, Nicolaus; Herrmann-Johns, Anne (Oncology research and treatment, 2024)
INTRODUCTION: This study explored qualitatively, in a sample of German hematologists working in clinical allogeneic hematopoietic stem cell transplantation (alloHSCT), perceptions of barriers and facilitators to participate in continuous medical education (CME), to provide detailed information on how to improve participation in CME activities related to alloHSCT, which may also be applicable to other areas of medicine. - METHODS: Based on a recruitment campaign of the German Association for Hematopoietic Stem Cell Transplantation (DAG-HSZT), 21 semi-structured telephone interviews were conducted, transcribed, and analyzed using framework analysis. - RESULTS: Three clusters of barriers were identified that explain why alloHSCT physicians may or may not participate in CME: individual constraints (e.g., better networking, young physicians being overwhelmed by the complexity of alloHSCT), structural constraints (e.g., time and financial issues, tailoring CME courses according to the targeted audience), and content-related constraints (e.g., requirement of CME sessions, provision of an overview of CME courses, more flexible offers). We discuss the ten most frequently raised issues, including the use of incentives and the need for support at the start of residency, staff shortages, and requirements for learning sessions. - CONCLUSION: There is a need for a paradigm shift in CME related to alloHSCT toward a more individualized and needs-based approach. Close monitoring of residents' needs and learning progress, as well as feedback systems, could help identify appropriate CME courses that should be integrated into a tiered learning system. CME should be more targeted to specific audiences (i.e., residents, fellows, and attendees) to provide training that is tailored to individual CME needs. On-demand courses can help balance work and family obligations. Finally, peer-reviewed, up-to-date information platforms should be expanded.
Gesehen am 07.02.2025